Central Bank of Ecuador, 1927: among Dictatorship, Revolution and Crisis - Cristian Naranjo Navas (Journal of Evolutionary Studies in Business, 2017)
On July 9th, 1925, a coup d’état overthrew the Ecuadorian government of the president Gonzalo S. Córdova. The Military Junta chose the new president, Dr. Isidro Ayora, who founded the Central Bank of Ecuador in 1927. The majority of historians emphasize the patriotic spirit of the military forces in order to eliminate the influence of private banks. Nonetheless, there is a less popular view of the Julian Revolution, which understands the coup d’état, and the foundation of the Central Bank of Ecuador, as the result of struggles between bankers due to controversies around currency emissions.